Impact of visceral fat ratio on sleep‐related erection: A retrospective study of elderly patients. (3rd June 2014) - Takeuchi, Motoi; Hisasue, Shin‐ichi; Hashimoto, Kohei; Tsukamoto, Taiji; Masumori, Naoya
<x xml:space="preserve">Abstract</x> Objectives To investigate the impact of visceral fat accumulation on the preoperative erectile function of elderly patients undergoing radical prostatectomy. Methods A total of 83 patients who underwent radical prostatectomy from August 2005 through August 2013 were included in the present study. Findings at preoperative computed tomography scanning and sleep‐related erection were used to determine the objective erectile function. Sleep‐related erection was measured with an erectometer during at least three nights, and we assessed the maximum penile circumferential change. The visceral fat ratio was calculated as the ratio of the visceral fat area to the total subcutaneous fat area on computed tomography images, and the influence of these parameters on preoperative erectile function was assessed. Results In simple linear regression analysis there was a strong correlation between the waist circumference and visceral fat ratio (P < 0.01). A visceral fat ratio of 55% was equivalent to a waist circumference of 85 cm, which is the standard value for central obesity in Japan. Furthermore, the factor that most negatively affected maximum penile circumferential change was the visceral fat ratio. In addition, only a visceral fat ratio of 55% or greater was a significant independent risk factor for declining maximum penile circumferential change in both univariate and multivariate analyses (P = 0.04 and 0.02, respectively). Conclusions The present study is the first to show the utility of the visceral fat ratio as an index of central obesity and the relationship with sleep‐related erection in elderly men.